Effect of Light and Electrostatic Gate at Oxide Interface LaFeO3–SrTiO3 at Room Temperature - Ripudaman Kaur; Anamika Kumari; Bibek Ranjan Satapathy; Anshu Gupta; Sanjeev Kumar; Suvankar Chakraverty (Advanced Physics Research, 2023)
Abstract Electrostatic gating and light illumination are two widely used stimuli for semiconductor devices. Two‐dimensional electron gas (2DEG) at oxide heterostructures has shown potential in optoelectronics due to its high optical response and gate tuning property. The appearance of high photoconductivity and persistent photoconductivity at the oxide heterostructure of two insulators LaFeO3 and SrTiO3 is shown here. The photoconductivity has been further tuned using positive and negative back gating. A large change in conductivity has been achieved under the simultaneous application of light and electrostatic gating. A few measurement protocols that manifest possible applications of this interface as memory and switching devices are implemented.